Preferred Learning Styles according to the Model “HONEY & MUMFORD” among Preparatory year Students at Shaqra University and its Relation to the level of Mathematics achievement - Alolyan, Fahad AbdulRahman (Journal of Educational and Psychological Sciences, 2020)
This research aimed to measure the style of learning, its percentage and its preferences among a sample of students of the preparatory year, and to reveal the correlation between the learning style and the level of academic achievement in mathematics (Mathematics Course 130).After confirming the validity and reliability, Applied the measure of (Honey and Mumford) on a sample of (53) students of the preparatory year students at the University of Shaqra.The results of the research showed that the Reflector style is the highest learning style preferred of the sample with 37.7% and its index is moderate. The Pragmatist style came second in the standings of preference by 22.6% and its index is moderate, followed by the Theorist style by 20.8% and index is moderate, and finally came the activity style by 18.9% and strong index, the research also found that the Reflector style came in the first standing of preference among low and medium achievement students, where the percentage of the highest style of students reached 40.0%, 39.3% respectively and the strength of its index (moderate) in both categories, where the percentage was the highest pattern for students 40.0%, 39.3% respectively and the strength of its index (moderate) in both categories, while came Practical style ranked first in standing of preference among High-achieving students, with a higher student style of 60.0%,The results also showed that there were no statistically significant differences in the study sample in the achievement of the course (130 mathematics) according to the learning style according to the (Honey and Mumford) measure.In light of these results, the researcher recommended:Provide a suitable classroom environment to diversify the teaching experiences in theteaching of the preparatory year students according to their learning styles, and use of various teaching methods and strategies, specially for reflective learning style.
Keywords: Learning Styles; Honey & Mumford; “Honey & Mumford” Model; Mathematics achievement; Preparatory year